Community Empowerment Balalak in Landak Regency, West Kalimantan Province, Indonesia - Herlan; Elyta; Al Qadrie, Syarif Redha Fachmi (MultiTech Publisher, 2024)
This research tries to analyze the empowerment of the Balalak community in the Landak Regency. By uncovering the challenges and opportunities that exist in the process. A study of community empowerment as facilitators in Balalak highlights how communities can empower institutions to meet needs by encouraging development. By examining regional community empowerment, this research provides insight for stakeholders and policymakers. This research is qualitative research with an exploratory approach; The use of an exploratory approach in this research aims to analyze more deeply and describe the circumstances of the phenomena that occur and are directly related to the situation or place. It is hoped that the research results will provide in-depth insight into Community Empowerment to improve the sustainability of development at the local level. With this approach, this research not only tries to detail the concept and role of Community Empowerment through Balalak Local Wisdom but also tries to understand its implementation in everyday community practice. Through these steps, it is hoped that this research can positively contribute to the sustainable development literature and pave the way for similar developments in various local contexts.